Grenzüberschreitungen – Migration, Heirat und staatliche Regulierung im europäischen Grenzregime: Eine Ethnographie - Gutekunst, Miriam (transcript, 2018)
Within the context of the »family reunion«, new border situations are developing far away from Europe's geographical external borders.